Two-dimensional facial measurements for anterior tooth selection in complete denture treatment - Chunhabundit P. (2023)
Purpose: Anterior tooth selection is one of the most challenging parts in determining tooth dimensions and critical to the aesthetic aspect of the complete denture treatment. However, the methods for anterior tooth size selection using facial measurements are still controversial. This study aimed to investigate the relationship between dental measurements and facial measurements, and to establish the anterior tooth size prediction equation using facial dimensions in the Thai population for the complete denture treatment. Materials & methods: One hundred and twenty-five Thai participants (53 men and 72 women) aged 18–35 years old with Angle class I occlusion, did not currently undergo orthodontic treatment, had normal alignment on the maxillary anterior teeth, no attrition, abrasion, proximal restoration or prosthesis were investigated. One frontal facial photograph and one dental photograph of each participant were made using an image analyzing program (ImageJ version 1.53b) to measure the six horizontal facial distances, five vertical facial distances and three dental distances as 2D facial and dental measurements. Pearson correlation and multiple linear regression analysis were performed. Results: The difference of facial and dental measurements between men and women were statistically significant (P < .001). Interpupillary width, interlateral canthal width, intercommissural width and bizygomatic width were correlated to dental measurements in both sexes. Intermedial canthal width and lip thickness were correlated to dental measurements in women. Face length and lateral canthus to lower border of face were correlated to dental measurements in men. Prediction equations of each dental measurement were established using only horizontal facial dimension and using both horizontal and vertical facial dimensions. Conclusions: Facial and dental dimensions are sex-dependent. Facial measurements can be applied in a regression equation to predict dental measurements. Adding vertical dimensions of facial measurements to the prediction equations of anterior tooth size selection results in a higher R squared to 0.444. This finding can be used as a tool for anterior tooth size selection in the complete denture treatment.